LITERATURE – HISTORY – DIDACTICS. LECH SŁOWIŃSKI’S RESEARCH ON THE HISTORY OF THE DIDACTICS OF LITERATURE - Podemska-Kałuża, Anna (Prace Polonistyczne, 2022)
The article presents the academic achievements of Professor Lech Słowiński – a historian of Polish literature, researcher of the history of education (including Polish language and literature education), professor of the Adam Mickiewicz University in Poznań, and for many years the head of the Department of the Methodology of Polish Language and Literature Education at the Institute of Polish Philology. It outlines Słowiński’s research interests and fascinations, stressing that he was, above all, the author of numerous academic texts on the teaching of Polish literature and language in various historical periods. Examining Słowiński’s academic research, the author accentuates his strategy of protecting from oblivion the names and achievements of important individuals who contributed to the preservation of Polish literature and culture during the partitions. The aim of the article is also to shed light on Lech Słowiński’s relatively numerous academic publications that can be situated outside literary studies. These important biographical, historical, and anthropological texts have for many years influenced the cultural and regional awareness of the successive generations of citizens of Poznań and the inhabitants of Greater Poland.